2014
DOI: 10.1088/0004-637x/786/2/83
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two- And Three-Dimensional Neutrino-Hydrodynamics Simulations of Core-Collapse Supernovae

Abstract: We present numerical results on two-(2D) and three-dimensional (3D) hydrodynamic core-collapse simulations of an 11.2M ⊙ star. By changing numerical resolutions and seed perturbations systematically, we study how the postbounce dynamics is different in 2D and 3D. The calculations were performed with an energy-dependent treatment of the neutrino transport based on the isotropic diffusion source approximation scheme, which we have updated to achieve a very high computational efficiency. All the computed models i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
286
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(295 citation statements)
references
References 68 publications
(137 reference statements)
9
286
0
Order By: Relevance
“…The dynamic behavior of the accretion shock has not received the attention afforded the SASI and convection, but previous analyses using tracer particles from CHIMERA simulations has shown that much of the matter passing through the shock is directed toward the proto-NS in accretion streams (Chertkow et al 2012;Lentz et al 2012a). We notethat the one or two accretion streams that dominate the accretion in 2D simulations is not characteristic of 3D simulations, which exhibit more numerous but weaker accretion streams Tamborra et al 2013Tamborra et al , 2014Takiwaki et al 2014;Tamborra et al 2014;Abdikamalov et al 2015;Lentz et al 2015).…”
Section: Accretion Streamsmentioning
confidence: 92%
See 4 more Smart Citations
“…The dynamic behavior of the accretion shock has not received the attention afforded the SASI and convection, but previous analyses using tracer particles from CHIMERA simulations has shown that much of the matter passing through the shock is directed toward the proto-NS in accretion streams (Chertkow et al 2012;Lentz et al 2012a). We notethat the one or two accretion streams that dominate the accretion in 2D simulations is not characteristic of 3D simulations, which exhibit more numerous but weaker accretion streams Tamborra et al 2013Tamborra et al , 2014Takiwaki et al 2014;Tamborra et al 2014;Abdikamalov et al 2015;Lentz et al 2015).…”
Section: Accretion Streamsmentioning
confidence: 92%
“…Zeus+IDSA is fully Newtonian and the transport omits inelastic (energy exchanging) scattering in favor of the elastic versions. Early versions neglected n mt andn mt completely, but some recent works (Nakamura et al 2015;Takiwaki et al 2014) have included a leakage scheme for these species. Suwa et al (2010) ) progenitor with a n mt -n mt leakage scheme added.…”
Section: Other Axisymmetric Simulationsmentioning
confidence: 99%
See 3 more Smart Citations